2021
DOI: 10.2217/epi-2021-0296
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a lncRNA–miRNA–mRNA Network to Determine the Key Regulators of the Th1/Th2 Imbalance in Multiple Sclerosis

Abstract: Aim: The exact epigenetic mechanisms that determine the balance of T helper (Th)1 and Th2 cells and autoimmune responses in multiple sclerosis (MS) remain unclear. We aim to clarify these. Methods: A combination of bioinformatics analysis and molecular evaluations was utilized to identify master hub genes. Results: A competitive endogenous RNA network containing six long noncoding RNAs (lncRNAs), 21 miRNAs and 86 mRNAs was provided through enrichment analysis and a protein–protein interaction network. NEAT1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Furthermore, scientists found that NEAT1 regulates the expression of proinflammatory factors through the MAPK pathway [ 105 ]. Moreover, similar to the findings in MS, a role of NEAT1 in the Th1/Th2 imbalance was recently described in SLE [ 106 , 107 ]. PBMCs from 97 SLE patients and 50 healthy volunteers were studied, and higher expression of NEAT1 and a lower Th1/Th2 ratio were observed in the SLE group, which reflected upregulation of IL4 and downregulation of IFNγ [ 106 ].…”
Section: Autoimmune and Neurodegenerative Disorder Pathomechanisms Ca...supporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, scientists found that NEAT1 regulates the expression of proinflammatory factors through the MAPK pathway [ 105 ]. Moreover, similar to the findings in MS, a role of NEAT1 in the Th1/Th2 imbalance was recently described in SLE [ 106 , 107 ]. PBMCs from 97 SLE patients and 50 healthy volunteers were studied, and higher expression of NEAT1 and a lower Th1/Th2 ratio were observed in the SLE group, which reflected upregulation of IL4 and downregulation of IFNγ [ 106 ].…”
Section: Autoimmune and Neurodegenerative Disorder Pathomechanisms Ca...supporting
confidence: 84%
“…RUNX3 regulates the production of IFNγ in Th1 cells and IL4 in Th2 cells via TBX21 and GATA3, respectively. Dysregulation of the levels of both these miRNAs and their downstream targets consequently leads to an IFNγ(Th1)/IL4(Th2) imbalance, which plays an important role in the regulation of inflammation in MS [ 107 ].…”
Section: Autoimmune and Neurodegenerative Disorder Pathomechanisms Ca...mentioning
confidence: 99%
“…GATA3 is a transcription factor required for Th2 cell differentiation, which promotes the development of Th2 cells and prevents the proliferation of Th1 cells. Studies had reported that the expression of GATA3 in peripheral blood of MS patients decreased, while the increase of its expression reduced the severity of EAE ( 44 , 45 ). PI3K is widely expressed and participates in multiple inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Common target genes among either anxiolytic or anxiogenic highlighted miR are determined via the miRDB database, and their potential protein-protein interaction (PPI) network and key hub genes were constructed using the STRING database version 11.0 ( , accessed on 18 July 2022) with confidence scores of ≥0.9 as a threshold [ 13 , 14 ]. Moreover, specific interactions of each highlighted miR with the mRNA sequence of common target genes were also predicted by the TargetScan database to confirm better the possibility of miR-mRNA interactions ( , accessed on 21 August 2022) [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%